A thermosetting sheath material for 80-year life cable for nuclear power plants and its preparation method
By using thermoset sheathed materials made of EVA and maleic anhydride grafted poly4-methyl-1-pentene and other materials in nuclear power plant cables, the problem of short service life of nuclear power plant cables in radiated environments is solved, and significant results are achieved Improve anti-aging performance and extend service life.
Patent Information
- Application Number
- CN202311034658.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-17
AI Technical Summary
The cables in nuclear power plants have short service life and aging speed in extremely strong radiation environments, so it is difficult for the existing technology to effectively improve their anti-aging performance.
It is composed of EVA, maleic anhydride grafted poly4-methyl-1-pentene, vulcanizing agent, vulcanizing promoter, activator, softener, anti-aging agent, reinforcing agent, inorganic flame retardant and light stabilizer The thermoset sheath material improves the anti-aging performance of cable sheath material through specific ratios and processing processes.
It significantly improves the anti-aging performance of cable sheath materials for nuclear power plants, extends its service life, and can maintain good structural toughness and thermal stability in harsh radiation environments.
Smart Images

Figure BDA0004398569530000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, in particular to a thermosetting sheath material for a cable with a service life of 80 years used in a nuclear power station and a preparation method thereof. Background Art
[0002] With the rapid development of economy, human beings have an increasing demand for energy. The existing energy structure is dominated by fossil energy, which has the disadvantage of being non-renewable and can also produce greenhouse effect and damage the ecological environment.
[0003] We have never slackened our pursuit of clean and environmentally friendly energy. At present, clean energy such as wind energy, hydropower, and solar energy have been widely promoted and applied, but they all have certain limitations; nuclear energy, as a new energy source, is the new energy source that is most likely to replace traditional fossil energy and become the main energy base in the future.
[0004] Various types of wires and cables are needed for power transmission and connection of related equipment in nuclear power plants. However, the operating environment of cables in nuclear power plants is very harsh, and the extremely strong radiation puts a test on the service life and aging of cables. Summary of the invention
[0005] The purpose of the present invention is to overcome and supplement the deficiencies in the prior art, to provide a thermosetting sheath material for 80-year life cables for nuclear power plants and a preparation method thereof, and to further improve the anti-aging performance of cable sheath materials for nuclear power plants.
[0006] The technical solution adopted by the present invention is:
[0007] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0008] EVA 100 parts;
[0009] Maleic anhydride grafted poly-4-methyl-1-pentene 20-30 parts;
[0010] 3-5 parts of vulcanizing agent;
[0011] 1 to 3 parts of vulcanization accelerator;
[0012] 2 to 4 parts of activator;
[0013] 4-8 parts of softener;
[0014] 5-10 parts of antioxidant;
[0015] 2 to 6 parts of reinforcing agent;
[0016] 150-180 parts of inorganic flame retardant;
[0017] 1 to 2 parts of light stabilizer.
[0018] Preferably, the thermosetting sheath material for the 80-year life cable for nuclear power plants, wherein: the vulcanizing agent is DCP.
[0019] Preferably, in the thermosetting sheath material for the 80-year life cable for nuclear power plants, the vulcanization accelerator is TAIC.
[0020] Preferably, in the thermosetting sheath material for the 80-year life cable for nuclear power plants, the activator is magnesium oxide.
[0021] Preferably, in the thermosetting sheath material for 80-year life cables for nuclear power plants, the softener is a mixture of paraffin and stearic acid in a mass ratio of 1:1.
[0022] Preferably, the thermosetting sheath material for 80-year life cables for nuclear power plants, wherein: the antioxidant is a mixture of antioxidants 445, 405 and antioxidant 1010, with a mass ratio of 1:1:1; the reinforcing agent is a mixture of gas-phase anthracene oil carbon black and nano-onion carbon in a mass ratio of 1:2; the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione, with a mass ratio of 1:1.
[0023] Preferably, the thermosetting sheath material for 80-year life cables for nuclear power plants, wherein: the inorganic flame retardant comprises 35-40% magnesium hydroxide, 25-30% aluminum silicate and 30-40% Zr5Si3B.
[0024] Preferably, the thermosetting sheath material for the 80-year life cable for nuclear power plants comprises: the thermosetting sheath material further comprising 6-10 parts of propylene-styrene-butadiene copolymer fiber filaments.
[0025] Preferably, the thermosetting sheath material for the 80-year life cable for nuclear power plants comprises: the thermosetting sheath material further comprising 1-3 parts of NN dimethyl salicylamide and 4-7 parts of acetylated lignin.
[0026] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0027] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio;
[0028] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, and the upper top bolt is lowered. The internal mixing temperature is 120-130°C, and the internal mixing time is 2-3 minutes. During this period, the upper top bolt is lifted three times; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4-5 minutes. During this period, the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to the twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0029] 3) Secondary mixing: adding the primary mixed material obtained in step 2), vulcanizing agent, vulcanization accelerator, activator, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin into an internal mixer, lowering the top bolt, the internal mixing temperature is 100-105° C., the internal mixing time is 110-120 seconds, during which the top bolt is lifted twice to make the materials more evenly dispersed, finally lifting the top bolt, opening the turning hopper, turning out the mixed material, controlling the discharging temperature within 110° C., and transferring to the open mixer for thin rolling;
[0030] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0031] EVA is a mixture of Formosa Plastics 7320M and BASF 5110J in a mass ratio of 1:1.5. It has excellent flow and processing properties at high temperatures, and has excellent mechanical properties and wear resistance at room temperature after cross-linking. Unlike plastic nuclear power sheath materials, it has a relatively excellent bending radius and has great advantages under certain specific laying conditions. It can also maintain a relatively stable structure under irradiation conditions.
[0032] Since Mg(OH)2 releases crystal water and magnesium oxide when heated at 300-350℃, absorbing a large amount of heat, the water vapor produced by the dehydration of Mg(OH)2 can dilute combustible gases and black smoke, causing the carbon black particles to oxidize into gas at high temperatures, thereby achieving a flame retardant effect. When a large amount of Mg(OH)2 is added, the physical and mechanical properties of the rubber compound will deteriorate, so Mg(OH)2 with very fine particle size and surface treated with coupling agent is selected, thereby improving the affinity between Mg(OH)2 and EVA and other compounding agents, making the Mg(OH)2 added to EVA more evenly dispersed, and improving the flame retardant effect of Mg(OH)2 on EVA and the physical and mechanical properties of the mixed rubber compound.
[0033] The softener is a mixture of paraffin wax and stearic acid in a mass ratio of 1:1. Paraffin wax plays a good lubricating role in the system, reducing internal friction, and migrates to the surface after vulcanization to form a physical protective layer, which also performs well during extrusion demolding; stearic acid is adsorbed on the surface of magnesium oxide and can react to produce a magnesium salt accelerator that is soluble in the rubber compound, thereby improving solubility.
[0034] The antioxidant is a mixture of antioxidant 445, 405 and antioxidant 1010 in a ratio of 1:1:2. This ratio is the best choice for the test and has excellent performance in the aging test.
[0035] The reinforcing agent is a mixture of gas-phase anthracene oil carbon black and nano-onion carbon in a mass ratio of 1:2. Because of the aromatic hydrocarbon compounds adsorbed on the surface of gas-phase anthracene oil carbon black, it can be observed that it has a more obvious effect of inhibiting radiation oxidation cracking when irradiated with air; at the same time, it has a great effect on maintaining the thermal stability of EVA after irradiation; when selecting CNO (nano-onion carbon), ND (nano-diamond) was compared simultaneously. Both have the same 10nm structural requirement and have better structural stability than other structures, but the existence of inherent defects in the material causes the nano-carbon material to show a decline in structural stability at a lower dose. Further comparison of sp3 structure ND and sp2 structure CNO found that sp3 will transform into sp2 structure under irradiation conditions, while sp2 structure itself has better stability. Therefore, 10nm nano-onion carbon was selected.
[0036] The light stabilizers are UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione, with a mass ratio of 1:1. In order to prevent ultraviolet rays from damaging the structure of the sheath material under irradiation conditions, an appropriate proportion of ultraviolet absorber is added, which can strongly absorb ultraviolet rays and has good thermal stability. It will not change due to heat even during processing, has low thermal volatility, and has good dispersibility and chemical stability.
[0037] EVA is a polymer with a linear structure. Through the combination of EVA and maleic anhydride grafted poly-4-methyl-1-pentene, the linear molecules are connected to each other to form a network structure, thereby improving the thermal decomposition resistance and chemical resistance of EVA as the main material, thereby improving its anti-aging ability. At the same time, it can significantly improve the toughness inside the thermosetting sheath material, thereby increasing its strength in harsh environments for a long time.
[0038] Propylene-styrene-butadiene copolymer is a random copolymer, and its synthesis method is the same as that of polybutadiene. It is only necessary to mix the three monomers in a designed proportion during the synthesis to start polymerization. Propylene-styrene-butadiene copolymer fiber has the excellent mechanical strength of polybutadiene, and also has excellent toughness and impact strength. The flexibility and strength of the thermosetting sheath material are improved by adding propylene-styrene-butadiene copolymer.
[0039] After combining with EVA, N,N-dimethyl salicylamide can prevent the thermosetting sheath material from hardening and yellowing after being irradiated, so as to maintain good structural toughness and thus ensure the service life of the sheath material. After the cross-linking reaction between N,N-dimethyl salicylamide and EVA, it can capture peroxyl radicals to inhibit chain initiation reaction and chain growth reaction, thereby terminating the free radical chain reaction and achieving the purpose of anti-aging. The heat resistance of the sheath material is improved by acetylation-modified lignin, and the mechanical properties and water resistance are also significantly enhanced.
[0040] Advantages of the present invention:
[0041] (1) The thermosetting sheath material for 80-year life cables for nuclear power plants of the present invention improves the heat decomposition resistance and chemical resistance of EVA as the main material by combining EVA and maleic anhydride grafted poly-4-methyl-1-pentene, thereby improving its anti-aging ability. At the same time, the toughness inside the thermosetting sheath material can be significantly improved, thereby improving its strength in harsh environments for a long time.
[0042] (2) The thermosetting sheath material for 80-year life cables for nuclear power plants of the present invention comprises a softener which is a mixture of paraffin wax and stearic acid in a mass ratio of 1:1. The paraffin wax has a good lubricating effect in the system, reduces internal friction, migrates to the surface after vulcanization, forms a physical protective layer, and also performs well during extrusion demolding. Stearic acid is adsorbed on the surface of magnesium oxide and can react to produce a magnesium salt accelerator soluble in the rubber material, thereby improving solubility. The antioxidant is a mixture of antioxidants 445, 405 and antioxidant 1010 in a ratio of 1:1:2, which is the optimal choice in the test and has excellent performance in the aging test. The reinforcing agent is a mixture of gas-phase anthracene oil carbon black and nano-onion carbon in a mass ratio of 1:2. Since the gas-phase anthracene oil carbon black has aromatic hydrocarbon compounds adsorbed on its surface, a more obvious effect of inhibiting radiation oxidation cracking can be observed during air irradiation. At the same time, it has a great effect on continuing to maintain the thermal stability of EVA after irradiation.
[0043] (3) In the thermosetting sheath material for the 80-year life cable for nuclear power plants of the present invention, N,N-dimethyl salicylamide, when combined with EVA, can prevent the thermosetting sheath material from becoming hard and yellow after being irradiated, so as to maintain good structural toughness, thereby ensuring the service life of the sheath material; the heat resistance of the sheath material is improved by the modified lignin, and the mechanical properties and water resistance are also significantly enhanced. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments.
[0045] The manufacturers of raw materials used in the embodiments and comparative examples are as follows: the manufacturer of EVA5110J is Formosa Plastics, the manufacturer of EVA7320M is BASF, the manufacturer of vulcanizing agent DCP is Jiangsu Daoming Chemical Co., Ltd., the manufacturer of vulcanization accelerator TAIC is Zhejiang Huangyan Zhedong Rubber Additive Co., Ltd., the manufacturer of activator magnesium oxide is Yingkou Zhongxin Mining, the paraffin wax of softener is Sinopec No. 62 granular wax, the manufacturer of stearic acid is Shandong Zhongwang, the manufacturer of reinforcing agent is Tianjin Huaran Chemical, and the manufacturer of inorganic flame retardant magnesium hydroxide is Zehui Chemical.
[0046] Example 1
[0047] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0048] 60 parts of EVA5110J; 40 parts of EVA7320M; 20 parts of maleic anhydride grafted poly-4-methyl-1-pentene; 3 parts of vulcanizing agent DCP; 2 parts of TAIC; 4 parts of magnesium oxide; 5 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 6 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 4 parts of a mixture of vapor phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 160 parts of an inorganic flame retardant, including 35% magnesium hydroxide, 25% aluminum silicate and 40% Zr5Si3B; 1 part of a light stabilizer, the light stabilizer including UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 6 parts of propylene-styrene-butadiene copolymer fiber, 1 part of NN dimethyl salicylamide, and 4 parts of acetylated lignin. 7 parts of maleic anhydride and 0.3 parts of dicumyl peroxide are mixed according to a formula ratio, and completely dissolved with acetone to obtain a solution. The solution is then poured into 100 parts of weighed poly-4-methyl-1-pentene, and heated and stirred for 10 minutes with a high-speed mixer to fully mix. The mixture is added to a twin-screw extruder and melt-extruded to obtain maleic anhydride grafted poly-4-methyl-1-pentene, and the extrusion temperature is 180°±5°C.
[0049] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0050] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio;
[0051] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0052] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber, the NN dimethyl salicylamide and the acetylated lignin are added to the internal mixer, the upper plug is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper plug is lifted twice to make the materials more evenly dispersed, and finally the upper plug is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0053] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0054] Example 2
[0055] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0056] EVA5110J 60 parts; EVA7320M 40 parts; Maleic anhydride grafted poly 4-methyl-1-pentene 25 parts;
[0057] 4 parts of vulcanizing agent DCP; 2 parts of vulcanization accelerator TAIC; 3 parts of magnesium oxide; 6 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 7 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 5 parts of a mixture of gas-phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 160 parts of an inorganic flame retardant, 37% magnesium hydroxide, 28% aluminum silicate and 35% Zr5Si3B; 2 parts of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 8 parts of propylene-styrene-butadiene copolymer fiber, 2 parts of NN dimethyl salicylamide, and 5 parts of acetylated lignin.
[0058] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0059] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio;
[0060] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0061] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber, the NN dimethyl salicylamide and the acetylated lignin are added to the internal mixer, the upper plug is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper plug is lifted twice to make the materials more evenly dispersed, and finally the upper plug is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0062] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0063] Example 3
[0064] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0065] EVA5110J 60 parts; EVA7320M 40 parts; Maleic anhydride grafted poly 4-methyl-1-pentene 30 parts;
[0066] 5 parts of vulcanizing agent DCP; 3 parts of vulcanization accelerator TAIC; 4 parts of magnesium oxide; 8 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 10 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 6 parts of a mixture of gas-phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 180 parts of an inorganic flame retardant, 40% magnesium hydroxide, 30% aluminum silicate and 30% Zr5Si3B; 2 parts of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 10 parts of propylene-styrene-butadiene copolymer fiber, 3 parts of NN dimethyl salicylamide, and 7 parts of acetylated lignin.
[0067] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0068] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio;
[0069] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0070] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber, the NN dimethyl salicylamide and the acetylated lignin are added to the internal mixer, the upper plug is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper plug is lifted twice to make the materials more evenly dispersed, and finally the upper plug is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0071] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0072] Comparative Example 1
[0073] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0074] 60 parts of EVA5110J; 40 parts of EVA7320M; 3 parts of vulcanizing agent DCP; 2 parts of TAIC; 4 parts of magnesium oxide; 5 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 6 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 4 parts of a mixture of vapor anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 160 parts of an inorganic flame retardant, including 35% magnesium hydroxide, 25% aluminum silicate and 40% Zr5Si3B; 1 part of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 6 parts of propylene-styrene-butadiene copolymer fiber, 1 part of NN dimethyl salicylamide, and 4 parts of acetylated lignin.
[0075] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0076] 1) EVA, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin are weighed according to the ratio;
[0077] 2) Primary mixing: EVA and inorganic flame retardant are placed in a mixer, the top bolt is lowered, the mixer temperature is 125°C, the mixer time is 2 minutes, and the top bolt is lifted three times during the mixing period; then the top bolt is lifted, and the softener, antioxidant and reinforcing agent are placed in the mixer for mixing for 4 minutes, during which the top bolt is lifted three times, and finally the top bolt is lifted, the flip hopper is opened, the mixed material is turned out, and the mixed material is transferred to the twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0078] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber, the NN dimethyl salicylamide and the acetylated lignin are added to the internal mixer, the upper plug is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper plug is lifted twice to make the materials more evenly dispersed, and finally the upper plug is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0079] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0080] Comparative Example 2
[0081] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0082] 60 parts of EVA5110J; 40 parts of EVA7320M; 25 parts of maleic anhydride grafted poly-4-methyl-1-pentene; 4 parts of vulcanizing agent DCP; 2 parts of vulcanization accelerator TAIC; 3 parts of magnesium oxide; 6 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 7 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 5 parts of a mixture of gas-phase anthracene oil carbon black and nano-onion carbon in a mass ratio of 1:2; 160 parts of an inorganic flame retardant, 37% magnesium hydroxide, 28% aluminum silicate and 35% Zr5Si3B; 2 parts of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 2 parts of NN dimethyl salicylamide and 5 parts of acetylated lignin.
[0083] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0084] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio;
[0085] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0086] 3) Secondary mixing: Add the primary mixed material obtained in step 2), vulcanizing agent, vulcanization accelerator, activator, light stabilizer, NN dimethyl salicylamide and acetylated lignin into an internal mixer, lower the top bolt, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the top bolt is lifted twice to make the materials more evenly dispersed, finally lift the top bolt, open the turning hopper, turn the mixed material out, control the discharging temperature within 110° C., and transfer to the open mixer for thin rolling;
[0087] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0088] Comparative Example 3
[0089] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0090] EVA5110J 60 parts; EVA7320M 40 parts; Maleic anhydride grafted poly 4-methyl-1-pentene 30 parts;
[0091] 5 parts of vulcanizing agent DCP; 3 parts of vulcanization accelerator TAIC; 4 parts of magnesium oxide; 8 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 10 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 6 parts of a mixture of gas-phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 180 parts of an inorganic flame retardant, 40% magnesium hydroxide, 30% aluminum silicate and 30% Zr5Si3B; 2 parts of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 10 parts of propylene-styrene-butadiene copolymer fiber filaments, and 3 parts of NN dimethyl salicylamide.
[0092] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0093] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, and NN dimethyl salicylamide were weighed according to the ratio;
[0094] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0095] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber, and the NN dimethyl salicylamide are added to the internal mixer, the upper top bolt is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper top bolt is lifted twice to make the materials more evenly dispersed, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0096] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0097] Comparative Example 4
[0098] A thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant, wherein: the thermosetting sheath material comprises the following components in parts by weight:
[0099] EVA5110J 60 parts; EVA7320M 40 parts; Maleic anhydride grafted poly 4-methyl-1-pentene 30 parts;
[0100] 5 parts of vulcanizing agent DCP; 3 parts of vulcanization accelerator TAIC; 4 parts of magnesium oxide; 8 parts of a mixture of paraffin and stearic acid in a mass ratio of 1:1; 10 parts of a mixture of antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; 6 parts of a mixture of gas-phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; 180 parts of an inorganic flame retardant, 40% magnesium hydroxide, 30% aluminum silicate and 30% Zr5Si3B; 2 parts of a light stabilizer, the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:1; 10 parts of propylene-styrene-butadiene copolymer fiber filaments, and 7 parts of acetylated lignin.
[0101] A method for preparing a thermosetting sheath material for a cable with an 80-year service life for a nuclear power plant, comprising the following steps:
[0102] 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber and acetylated lignin are weighed according to the ratio;
[0103] 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, the upper top bolt is lowered, the internal mixing temperature is 125°C, the internal mixing time is 2 minutes, and the upper top bolt is lifted three times during the mixing period; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4 minutes, during which the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to a twin-screw extruder for extrusion into long strips, and then left to cool to room temperature;
[0104] 3) Secondary mixing: the primary mixed material obtained in step 2), the vulcanizing agent, the vulcanization accelerator, the activator, the light stabilizer, the propylene-styrene-butadiene copolymer fiber and the acetylated lignin are added to the internal mixer, the upper top bolt is lowered, the internal mixing temperature is 100° C., the internal mixing time is 110 s, during which the upper top bolt is lifted twice to make the materials dispersed more evenly, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, the discharging temperature is controlled within 110° C., and the mixture is transferred to the open mixer for thin rolling;
[0105] 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
[0106] UV aging test:
[0107] The thermosetting sheath materials prepared in the above-mentioned embodiments and comparative examples were subjected to an ultraviolet aging resistance test. The test conditions were as follows: a 6kW xenon lamp was used for irradiation and water was sprayed at a water pressure of 0.12 to 0.15 MPa. The ultraviolet irradiation was performed in a cycle of 120 minutes, of which 18 minutes were for simultaneous water spraying and irradiation, and the other 102 minutes were for single illumination, for a total of 2000 hours of exposure. The samples were then placed at room temperature for 20 hours, and their appearance was observed to determine whether there were cracks. The tensile strength and elongation at break were tested before and after the experiment, and the rate of change of the tensile strength and elongation at break, i.e., the ratio of the tensile strength and elongation at break after the experiment to those before the experiment, was calculated.
[0108] The performance test results of Examples 1-3 and Comparative Examples 1-4 are listed below in Table 1.
[0109] Table 1 Performance test results of thermosetting sheath materials obtained from Examples 1-3 and Comparative Examples 1-4
[0110]
[0111] The material was subjected to a 90°C thermal aging assessment test. The test method of "IEC60216-1:2013" was adopted, and four temperature points (180°C, 165°C, 150°C, and 135°C) were selected for aging tests. The aging time when the retention rate of the elongation at break after aging was 50% was taken as the termination time. Finally, according to the Arrhenius equation, it was calculated that under a 90°C environment, the service life of Example 1 can reach 80.3 years. The service life of Example 2 tested by the same method was 84.9 years, and the service life of Example 3 was 81.2 years. Comparative Example 1 was completely brittle in the life assessment test, the service life of Comparative Example 2 was 6 years, and the service life of Comparative Examples 3 and 4 was 8 years.
[0112] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A thermosetting sheath material for 80-year life cables for nuclear power plants, characterized in that: The thermosetting sheath material comprises the following components in parts by weight: EVA 100 parts; Maleic anhydride grafted poly-4-methyl-1-pentene 20-30 parts; 3-5 parts of vulcanizing agent; 1 to 3 parts of vulcanization accelerator; 2-4 parts of activator; 4-8 parts of softener; 5-10 parts of antioxidant; 2 to 6 parts of reinforcing agent; 150-180 parts of inorganic flame retardant; 1-2 parts of light stabilizer; 6-10 parts of propylene-styrene-butadiene copolymer fibers; NN dimethyl salicylamide 1-3 parts; 4-7 parts of acetylated lignin.
2. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The vulcanizing agent is DCP.
3. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The vulcanization accelerator is TAIC.
4. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The activator is magnesium oxide.
5. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The softener includes paraffin and stearic acid in a mass ratio of 1:
1.
6. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The antioxidant includes antioxidants 445, 405 and antioxidant 1010 in a mass ratio of 1:1:1; the reinforcing agent includes gas-phase anthracene oil carbon black and nano onion carbon in a mass ratio of 1:2; the light stabilizer includes UV-326 and (R)-4-phenyloxyazacyclopentane-2,5-dione in a mass ratio of 1:
1.
7. The thermosetting sheath material for 80-year life cable for nuclear power plant according to claim 1, characterized in that: The inorganic flame retardant comprises 35-40% magnesium hydroxide, 25-30% aluminum silicate and 30-40% Zr5Si3B.
8. A method for preparing a thermosetting sheath material for a cable with a service life of 80 years for a nuclear power plant according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) EVA, maleic anhydride grafted poly-4-methyl-1-pentene, vulcanizing agent, vulcanization accelerator, activator, softener, antioxidant, reinforcing agent, inorganic flame retardant, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin were weighed according to the ratio; 2) Primary mixing: EVA, maleic anhydride grafted poly-4-methyl-1-pentene, and inorganic flame retardant are placed in an internal mixer, and the upper top bolt is lowered. The internal mixing temperature is 120-130°C, and the internal mixing time is 2-3 minutes. During this period, the upper top bolt is lifted three times; then the upper top bolt is lifted, and the softener, antioxidant, and reinforcing agent are placed in the internal mixing for 4-5 minutes. During this period, the upper top bolt is lifted three times, and finally the upper top bolt is lifted, the turning hopper is opened, the mixed material is turned out, and the mixed material is transferred to the twin-screw extruder for extrusion into long strips, and then left to cool to room temperature; 3) Secondary mixing: adding the primary mixed material obtained in step 2), vulcanizing agent, vulcanization accelerator, activator, light stabilizer, propylene-styrene-butadiene copolymer fiber, NN dimethyl salicylamide and acetylated lignin into an internal mixer, lowering the top bolt, the internal mixing temperature is 100-105° C., the internal mixing time is 110-120 seconds, during which the top bolt is lifted twice to make the materials more evenly dispersed, finally lifting the top bolt, opening the turning hopper, turning out the mixed material, controlling the discharging temperature within 110° C., and transferring to the open mixer for thin rolling; 4) Rolling and sheeting: Put the thin film into the three-roller rolling machine for rolling and cutting, and turn on the cooling water on the cooling drum. Pass the cut film through the cooling drum and then through the isolation powder tank to make the film.
Citation Information
Patent Citations
Anti-aging packaging adhesive for solar photovoltaic panel
CN105018002A
Preparation method for acetylated lignin-modified unsaturated polyester conductive foam
CN106009578A